The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1479-5876-9-156
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation and downregulation of SLC22A18 are associated with the development and progression of human glioma

Abstract: BackgroundDownregulation of the putative tumor suppressor gene SLC22A18 has been reported in a number of human cancers. The aim of this study was to investigate the relationship between SLC22A18 downregulation, promoter methylation and the development and progression of human glioma.MethodSLC22A18 expression and promoter methylation was examined in human gliomas and the adjacent normal tissues. U251 glioma cells stably overexpressing SLC22A18 were generated to investigate the effect of SLC22A18 on cell growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
(30 reference statements)
2
31
0
Order By: Relevance
“…However, there are few studies on its effect on glioma cancer cells (6). Gliomas are the most primary prevalent and aggressive form of intracranial tumors affecting adults 40-60 years of age (7,8). Despite multidisciplinary treatments including surgery, chemotherapy and radiotherapy, it has a poor prognosis with a median survival of less than 15 months (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies on its effect on glioma cancer cells (6). Gliomas are the most primary prevalent and aggressive form of intracranial tumors affecting adults 40-60 years of age (7,8). Despite multidisciplinary treatments including surgery, chemotherapy and radiotherapy, it has a poor prognosis with a median survival of less than 15 months (9).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great progress has been made in diagnosing and treating glioma, but its recurrence after resection still makes long-term prognosis unsatisfactory. [1][2][3] Looking for new treatments and further studying its mechanism remain very important. With the development of nanotechnology, a new inorganic material, 1 nanoparticles (nano-HAPs), was found capable of inhibiting the proliferation of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Recently, we have found that SLC22A18 downregulation via promoter methylation was associated with the development and progression of glioma, that it represented a candidate biomarker, and that the elevated expression of SLC22A18 increased the sensitivity of U251 glioma cells to BCNU. 1,2,26 In recent years, SATB1 has attracted considerable attention because of its high expression in tumor tissues as a variety of malignancies, which suggests its important role in promoting tumor growth, invasion, and metastasis; it may also have potential value as a candidate for cancer therapy. [27][28][29] Our results showed that the expression of c-Met, SATB1, and Ki-67 protein decreased and that SLC22A18 protein in glioma U251 and SHG44 cells increased after the cells were treated with various concentrations of hydroxyapatite nanoparticles in vitro.…”
mentioning
confidence: 99%
“…PLAGL1 is thought to be a transcriptional regulator and has been associated with pheochromocytoma, a tumor of the adrenal grand [26]. SLC22A18 is a transporter of organic cations, and has been associated with glioma and breast cancer progression and survival [27,28]. WT1 plays an important role in normal development of the urogenital system, and is named after its association with Wilms’ tumor development [29].…”
Section: Discussionmentioning
confidence: 99%